Comparison of voluntary food intake and digestibility in swamp buffaloes and Ayrshire cattle - Baber, Richard Paul (The University of Edinburgh, 1983)
The voluntary food intake and digestibility in Swamp buffaloes and Ayrshire cattle were compared. Four animals of each species were used and offered a medium quality diet, AA6, or a lower quality diet, Viton 10, at an ambient temperature of 21°C or 31 °C. A double cross-over design was used so that every animal would be fed each diet at both temperatures. Water intake, respiration rate and serum thyroid hormone concentration were determined to indicate the degree of heat stress to which an animal was being subjected. Voluntary food intake of the AA6 diet was significantly greater by cattle than by the buffaloes. There was no significant difference between buffaloes and cattle in the intake of the Viton 10 diet. The buffaloes consumed significantly more of the Viton 10 than the AA6 diet, whereas in the cattle there was no significant difference between the intake of the AA6 and Viton 10 diets. Cattle consumed significantly less at the higher temperature than at the lower one, however, temperature had no significant effect upon food intake of the buffaloes. There was no significant difference between buffaloes and cattle in the Neutral detergent fibre or dry matter digestibility of either diet. Dry matter digestibility in both buffaloes and cattle was greater on the AA6 diet than on the Viton 10 diet, whereas Neutral Detergent fibre digestibility was greater for the Viton 10 diet than for the AA6 diet. Temperature did not affect dry matter or Neutral detergent fibre digestibility significantly in either species of animal or for either diet.
A comparison of voluntary food intake and digestibility in swamp buffaloes and Ayrshire cattle
Keywords: Annexe MSc Digitisation Project 2022 Block 50; Voluntary food intake; Digestibility; Temperature; Swamp buffaloes; Ayrshire cattle